ANALISIS KINERJA GASIFIER UNGGUN TETAP ALIRAN KE BAWAH MENGGUNAKAN UMPAN KAYU UNTUK MESIN PEMBANGKIT LISTRIK TENAGA GAS - Gaos, Yogi Sirodz; Putra, Hanang Agna Pradana; Bahry, Syamsul (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2015)
PERFORMANCE ANALYSIS OF FIXED BED GASIFIER USING FLOW DOWN PINE CHIPWOOD FOR GAS ENGINE POWER GENERATION. In recent years energy resources dwindling oil so it is necessary to replace it with renewable energy sources. Biomass is one of the renewable energy sources which has gasification technology, in which these technologies can transform wood into gas fuel (syngas). The research methodology is how to design and manufacture of; gasifier, cyclone and wet scrubber based on the needs of the gas engine performance. The apparatus for wood analysis by using Thermal Conductivity Detection (TCD) and Firing Ionization Detection (FID) to get the calorific value, proximate (containing of; moisture, ash, volatile matter and fixed carbon) and ultimate (containing of; carbon, hydrogen, nitrogen and oxygen) in the wood. Gas chromatography analyser is used to determine the syngas chemical composition and Thermocouple K-type (National Instrument) is used to obtain temperature distribution. From the test results in the data obtained in the temperature distribution in the drying zone of the gasifier at 41ºC, pyrolysis zone at 98 ºC, oxidation zone at 970 ºC and reduction zones at 63 ºC. Meanwhile, syngas temperature in the cyclone outlet is 36,8 ºC and in the wet scrubber outlet is 35,96ºC. Syngas chemical composition generated output gasifier as follows; CO=29,3%, H2=5,6%, CH4=1,03%, CO2=1,33%, and N2=47,35%, meanwhile on the output side of the cyclone; CO=28,05%, H2=4,15%, CH4= 0,44%, CO2= 1,39%, and N2= 49,61% and on the output side of the wet scrubber; CO= 25,63%, H2= 4,49% , CH4= 0,80%, CO2=1,72%, and N2= 51,01%.